Role of platelet activating factor as a mediator of inflammatory diseases and preterm delivery - Wahid, Hanan H.; Anahar, Fatin N.; Isahak, Nurul H.; Mohd Zoharodzi, Juwairiyah; Mohammad Khoiri, Siti N. L.; Mohamad Zainal, Nurul H.; Kamarudin, Norhidayah; Ismail, Hamizah; Mustafa Mahmud, Mohammed I. A. (Elsevier, 2024)
Nearly 70% of preterm deliveries occur spontaneously, and the clinical pathways involved include preterm labor and preterm premature rupture of membranes. Prediction of preterm delivery is considered crucial due to the significant effects of preterm birth on health and the economy at both the personal and community levels. Although similar inflammatory processes occur in both term and preterm delivery, the premature activation of these processes or exaggerated inflammatory response triggered by infection or sterile factors leads to preterm delivery. Platelet activating factor (PAF) is a phosphoglycerylether lipid mediator of inflammation that is implicated in infections, cancers, and various chronic diseases and disorders including cardiovascular, renal, cerebrovascular, and central nervous system diseases. In gestational tissues, PAF is proposed to mediate the inflammatory pathways that stimulate the effector mechanisms of labor, including myometrial contraction, cervical dilation, and fetal membrane rupture. Studies have shown that women with preterm labor and preterm premature rupture of membranes have increased levels of PAF in their amniotic fluid. In mice, the intrauterine or intraperitoneal administration of carbamyl PAF activates inflammation in gestational tissues, thereby eliciting preterm delivery. In this review, to the authors summarize recent research on PAF as an important inflammatory mediator in preterm delivery and in other inflammatory disorders, highlighting its potential value for prediction, intervention, and prevention of these diseases.